Printed wire antennas for wireless communications - Zhang, Yingbo (2008)
The printed wire antennas have wide applications in wireless communications in recent years. They have kept the attractive features of the conventional wire antennas such as wideband, simple feeding and efficient radiation, while having additional advantages of stability, accurate fabrication at high frequency and ease of designing matching circuits. In this thesis several printed wire antennas with different type of feedings have been designed, implemented and measured. They all have desirable characteristics such as compact size, wideband circularly polarization, and impedance matching. Both the calculated results and measured results are presented and they agree with each other quit well.